Utilization of palm oil sludge in poultry diet. 4. Inclusion of fresh or dried fermented palm oil sludge in native chickens diet - Sinurat, A.P; Purwadaria, T; Pasaribu, T; Darma, J; Bintang, I.A.K; Togatorop, M.H (Indonesian Journal of Animal and Veterinary Sciences, 2001)
Fermentation processes increase the protein of palm oil sludge and produce some useful enzymes. However, drying process, especially with heating often affects the nutritive values of feed ingredients and the enzymes activity. Therefore, this experiment was designed to study the responses of native chickens when fed ration containing fresh or dried fermented palm oil sludge(FPOS). Experimental diets with different levels of fresh or dried FPOS (5, 10 and 15% equal to dried FPOS) were  formulatedwith similar nutrient contents. A control diet with no FPOS was also included. Each treatment was replicated 5  times for 12weeks. Performances (body weight, feed consumption, feed conversion and mortality) of chickens were  recorded. Carcass yield,abdominal fat content, weight of liver and gizzard were measured at the end of feeding trial. Data  were subjected to analysis ofvariance and different between means were tested by orthogonal procedures. Results during the  starting period showed that,chickens fed FPOS diet gain more weight significantly than the control birds (298.1 vs. 264.7).  The dry matter intake of the dryFPOS diet was significantly better than the fresh FPOS diet (2.88 vs. 3.32). The FPOS  dietary levels did not affect body weightgain and dry matter intake of native chickens, significantly. However, increasing the  FPOS levels worsen the dry matterconversion (DCR) significantly. Data during 12 weeks trial showed mat the body weight  gain was not significantly affected bytreatments. The dry matter intake of the FPOS diets were significantly higher than the  control diet (3469 vs. 3065 g/bird), hencethe DCR of the control diet was significantly better than the FPOS diets (3.28 vs.  3.62). Feeding dry FPOS resulted in a betterDCR as compared to fresh FPOS (3.48 vs. 3.76), but not affected the dry matter  intake. The FPOS dietary levels did not affectbody weight gain and dry matter intake of native chickens, significantly.  However, inclusion of 5% FPOS in me diet gave betterDCR significantly, as compared with 15% FPOS (3.51 vs. 3.83).  Feeding dry or fresh FPOS (5 - 15%) did not significantlyaffect the mortality, carcass yield, abdominal fat levels, weight of  liver and weight of gizzard of native chickens. It is concludedthat dry FPOS was better than the fresh FPOS and could be  included in me native chickens diet up to 10%.   Key words: Palm oil sludge, fermentation, native chickens